Impact of Ethnocentrism and Other Factors on Willingness to Buy Chinese Cars - Siahaan, Ricky Humisar; Suhud, Usep; Purwohedi, Unggul (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
This study aims to determine the effect of ethnocentrism, animosity, product country image, and brand image on the willingness to buy Chinese car products. Data were collected from Chinese car users and potential car buyers. The purposive sampling technique was chosen in this study, which resulted in 300 respondents for analysis. Data were analysed using exploratory factor analysis and structural equation modelling. The results showed that ethnocentrism had a significant positive effect on animosity and had a significant negative effect on brand image, animosity had a significant negative effect on willingness to buy, the brand image had a positive and significant effect on willingness to buy, and product country image had a significant positive effect on brand image. Meanwhile, ethnocentrism and product country image do not affect willingness to buy. This study helps to improve our understanding of consumer behaviour regarding the purchase of foreign products.